An Analysis of EFL Teachers’ Perceptions on the Integration of TPACK in Teaching English at SMA-Man in Solok - Yolanda Andriany; Aryuliva Adnan (Universitas Negeri Padang, 2022)
This article deals with the integration of TPACK at SMA-MAN in Solok. The research undertaken aimed to know what are EFL teachers’ perceptions about TPACK in teaching English. This study was descriptive qualitatie research. The participants of the research were 20 English teachers at five schools in Solok. The instrumentation of this research were collected from questionnaire and interview that have done by the teachers. As for the points to the instrumentations there were aspect of TK, CK, PK, PCK, and TPACK. The findings of this research shows that EFL teachers have good perceptions about the integration of TPACK in teaching English.